Tuberculosis in children at Mbarara University Teaching Hospital, Uganda: diagnosis and outcome of treatment - Kiwanuka, Julius P. (African Health Sciences, 2002)
Background: The diagnosis of tuberculosis in children is difficult particularly in HIV infected children. The poor outcome following antituberculosis treatment usually reported in HIV infected children might be due, in part, to other HIV-related chronic diseases wrongly diagnosed as TB. Objective: The study examines the impact of HIV infection on the clinical features and diagnosis of children presenting with suspected tuberculosis in Mbarara University Teaching Hospital. It also examines the effect of various factors on the outcome of anti-TB treatment. Methods: Children presenting with suspected TB were prospectively enrolled. Clinical data were recorded and investigations included Mantoux test, chest X-ray, HIV test and Z-N staining of various specimens for AAFBs where available. Patients were treated with standard, short-course anti-TB therapy, and followed-up for six months. They were then classified as “good outcome” if they improved and “poor outcome” if they deteriorated or died whilst on treatment. Results: A total of 128 children were enrolled over an 18-month period. Four patients (3.1%) had a diagnosis of confirmed TB, 82 (64.1%) with “probable TB” and 42 (32.8%) with “suspected TB”. Of 88 patients tested 43 (48.9%) were HIV positive. HIV positive patients had a higher frequency of failure to thrive, digital clubbing, enlarged lymph nodes and hepatomegaly; and a lower frequency of positive Mantoux tests. HIV positive patients were less likely to be classified as “confirmed or probable TB” (c2 = 5.02, p = 0.025). Fifty-six patients had a good outcome, 12 had a poor outcome and 60 defaulted before completing six months of treatment. HIV positive children were more likely to have a poor outcome (relative risk = 9.58, 95% CI 1.32 – 69.46). A diagnosis of “confirmed or probable TB” was associated with a good outcome (relative risk for poor outcome = 0.14, 95% CI 0.05 – 0.36). Conclusion: HIV positive children with suspected TB frequently have signs that suggest the presence of other diseases such as Lymphocystic Interstitial Pneumonitis (LIP) and chronic bronchiectasis; and are less likely to have a diagnosis of “probable or confirmed TB” after investigations. Patients with an uncertain diagnosis of TB are less likely to improve on anti-TB therapy
Keywords: Childhood tuberculosis; HIV infection; Diagnosis; Outcome of treatment